ERGONOMICS AT SCHOOL: CONTRIBUTIONS TO THE DEVELOPMENT OF LEARNING (Fiep Bulletin - online, 2025)
This study addressed ergonomics in the school environment, highlighting its contributions to students' physical and psychological well-being and academic performance improvement. The research demonstrated that appropriate furniture, combined with elements such as lighting, ventilation, and temperature, is essential to prevent musculoskeletal problems and enhance concentration and motivation. The integration of educational technologies, such as mobile devices and virtual reality, reinforces the need for ergonomic practices that consider physical and cognitive aspects, avoiding discomfort and mental overload. However, the study revealed challenges in implementing these practices, especially in public schools, due to financial constraints, deficient infrastructure, and a lack of training for managers and teachers. To overcome these barriers, public policies promoting funding, professional development, and the adoption of ergonomic standards are essential. It concludes that school ergonomics is not only a tool for preventing physical problems but also a strategic factor for promoting an inclusive and efficient environment. Investing in ergonomics ensures students' health, comfort, and potential, contributing to educational quality and overall well-being.
Keywords: Ergonomics; School; Learning; Physical education